Geometrical complexity and crack trajectory based fatigue life prediction for a spur gear having tooth root crack. (November 2019) - Patil, Vivek; Chouhan, Vaibhav; Pandya, Yogesh
Abstract: The objective of the present study is to perform a three-dimensional crack propagation path analysis for different geometrical parameters of spur gear tooth and study its implications on fatigue life of gear. Most of the study for crack trajectories in gear tooth has relied on a 2-Dimensional platform to formalize these simulations which have resulted in undermining various factors encountered in the studies. This paper proposes a three-dimensional Boundary Element Method (BEM) based approach to generate the crack propagation trajectories. A three-dimensional linear elastic fracture mechanics based software; FRANC3D has been adopted to obtain the crack propagation path in a spur gear tooth root under influence of varying gear parameters. Crack Opening Displacement (COD) approach is used to determine the respective Stress Intensity Factor (SIF) for various modes. Moreover, the maximum tangential stress crack extension criterion is used to obtain the propagation paths. The fatigue crack in the gear tooth is subjected to constant amplitude moving load and the remaining service life is estimated by Forman-Newman-de Koning (FNK) model. The obtained fatigue life plots are compared with the previous studies in the literature to justify the simulative process. Highlights: Investigated crack propagation path for a spur gear tooth under cracked condition. Obtained non linear three dimensional crack trajectory for various geometrical complexities. Fatigue life estimation using Forman Newman de Koning (FNK) model The complete analysis is performed on three dimensional platform; Franc3d. Results obtained in close resemblance with previous crack propagation studies.